STUDY ON LITERACY NUMERACY TOWARDS STUDENTS’ LOGIC MATHEMATICS: A LITERATURE REVIEW - Pratiwi, Septia Ayu; Nofikusumawati Peni, Nur Robiah; Prabowo, Anggit (Jurnal Numeracy, 2024)
Numeracy literacy and mathematical logical thinking have a significant relationship in mathematics learning. Therefore, the study of this literacy examines the relationship between literacy, numeracy, and the development of students' logical thinking in the domain of mathematics education. This research aims to delineate the impact of numeracy literacy and logical thinking in shaping students' abilities to understand and apply logical principles in the context of mathematics, given the fundamental importance of literacy and numeracy skills. In this study, a literature review is employed to examine the relationship between literacy, numeracy, and logical thinking in the context of mathematics. The methodology used involves data collection, review processes, and in-depth analysis of scholarly articles sourced from Google Scholar, JSTOR, and PubMed. A total of 105 articles were analysed and categorized into the contexts of literacy, numeracy, and logical thinking in the context of mathematics. The research findings indicate the complexity of the interrelationship between literacy, numeracy, and logical thinking in mathematics education. This research contributes to offering insights into numeracy literacy and logical thinking for educators, researchers, and policymakers interested in enhancing the quality of mathematics education.